Us versus Them: The Debates on the Legislation of Same-Sex Marriage (1994 – 2015) in Taiwan. Issue 4 (21st March 2022) - Lee, I-Ching; Lin, Wei-Fang
ABSTRACT: Taiwan, the first country in Asia to provide same-sex couples a legal right to marriage, has witnessed furious debate on both sides. To understand this debate, we combined content analysis and the Linguistic Inquiry and Word Count (LIWC) method to capture themes and states of mind reflected in the news articles. Arguments based in human rights and reflecting heterosexual preferences which were observed elsewhere also dominated the discourses in Taiwan. First-person pronouns, positive and negative emotions, and differentiation were found to be associated with rights discourses and, in turn, support for same-sex marriage. The themes, the state of mind of the involved parties, and same-sex marriage legalization are further discussed.